Nano-Curcumin Inhibits Proliferation of Esophageal Adenocarcinoma Cells and Enhances the T Cell Mediated Immune Response - Milano, Francesca; Mari, Luigi; van de Luijtgaarden, Wendy; Parikh, Kaushal; Calpe, Silvia; Krishnadath, Kausilia (Frontiers in Oncology, 2013)
In Western countries the incidence of the esophageal adenocarcinoma (EAC) has risen at a more rapid rate than that of any other malignancy. Despite intensive therapies this cancer is associated with extreme high morbidity and mortality. For this reason, novel effective therapeutic strategies are urgently required. Dendritic Cell (DC)-based immunotherapy is a promising novel treatment strategy, which combined with other anti-cancer strategies has been proven to be beneficial for cancer patients. Curcumin (diferuloylmethane), is a natural polyphenol that is known for its anti-cancer effects however, in it’s free form, curcumin has poor bioavailability. The aim of this study was to investigate whether using a highly absorptive form of curcumin, dispersed with colloidal nano-particles, named Theracurmin would be more effective against EAC cells and to analyze if this new compound affects DC-induced T cell response. As a result, we show efficient uptake of nano-curcumin by the EAC cell lines, OE33 and OE19. Moreover, nano-curcumin significantly decreased the proliferation of the EAC cells, while did not affect the normal esophageal cell line HET-1A. We also found that nano-curcumin significanly upregulated the expression of the co-stimulatory molecule CD86 in DCs and significantly decreased the secretion of pro-inflammatory cytokines from in-vitro activated T cells. When we combined T cells with nano-curcumin treatment in OE19 and OE33, we found that the basic levels of T cell induced cytotoxicity of 6.4% and 4.1%, increased to 15% and 13%, respectively. In conclusion, we found that nano-curcumin is effective against EAC, sensitizes EAC cells to T cell induced cytotoxicity and decreases the pro-inflammatory signals from T cells. Combining DC immunotherapy with nano-curcumin is potentially a promising approach for future treatment of EAC.